2019
DOI: 10.1002/jbmr.3733
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Based Estimates of Cortical Bone Thickness and Porosity Are Associated With Nontraumatic Fractures in Postmenopausal Women: A Pilot Study

Abstract: Recent ultrasound (US) axial transmission techniques exploit the multimode waveguide response of long bones to yield estimates of cortical bone structure characteristics. This pilot cross‐sectional study aimed to evaluate the performance at the one‐third distal radius of a bidirectional axial transmission technique (BDAT) to discriminate between fractured and nonfractured postmenopausal women. Cortical thickness (Ct.Th) and porosity (Ct.Po) estimates were obtained for 201 postmenopausal women: 109 were nonfrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 75 publications
(192 reference statements)
2
35
0
1
Order By: Relevance
“…It can be noted that this approach was then extended to an inverse procedure providing estimates of two cortical parameters: Ct.Th and Ct.Po [29]. Inverse problem results obtained in [28] will be used as a baseline in the following.…”
Section: Instrumentation and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…It can be noted that this approach was then extended to an inverse procedure providing estimates of two cortical parameters: Ct.Th and Ct.Po [29]. Inverse problem results obtained in [28] will be used as a baseline in the following.…”
Section: Instrumentation and Datamentioning
confidence: 99%
“…Recently, estimates of Ct.Th and Ct.Po, derived from guided wave spectrum measured by bi-directional axial transmission (BDAT), have been tested in a pilot clinical study [28]. In this, study, Ct.Po discrimination between fractured and non-fractured patients, was found similar to DXA, with an AUC, Area Under the Receiver Operator Characteristic (ROC) Curve, equal to 71%, after adjustement performed according to age, Body Mass Index (BMI) and cortisone treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] Frequency-dispersive guided waves have been extensively used for cortical bone characterization. [28][29][30] However, only few studies notice and discuss the influence of guided waves on CEUS, even if the guided waves have been used to detect and trap microdroplets and gas bubbles in acoustic manipulation. [31][32][33] In our previous studies, we observed the microbubbles' nonlinear scattering altered by the guided waves under a fixed phase transmission, which is verified by using the cross-validations of simulated and measured results from bone cortex and plate model.…”
Section: Introductionmentioning
confidence: 99%